PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA KOPITIAM LANGKAH KANAN DI KOTA PEKANBARU - Tiagita Syahbina Ayuningtias; Taufiqurrahman Taufiqurrahman; Sri Wahyuni Wildah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to determine the effect of service quality and price on customer loyalty throughcustomer satisfaction at Kopitiam Langkah Kanan in Pekanbaru. In this study, data collected from100 respondents who had visited the establishment more than twice, were aged 17 years or older,and resided in Pekanbaru were analyzed using SEM-PLS. The results indicate that service qualityand price have a positive and significant effect on customer satisfaction at Kopitiam Langkah Kananin Pekanbaru; service quality and price have a positive and significant effect on customer loyalty atKopitiam Langkah Kanan in Pekanbaru; customer satisfaction has a positive and significant effecton customer loyalty at Kopitiam Langkah Kanan in Pekanbaru; and customer satisfaction mediatesthe relationship between service quality and price and customer loyalty at Kopitiam Langkah Kananin Pekanbaru. Keywords: Product Quality, Price, Customer Satisfaction, Customer Loyalty